2012
DOI: 10.1177/1071181312561001
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Usability Problems of Blood Glucose Tracking Apps for Older Adult Users

Abstract: Almost two-thirds of adults aged 65 and older in the United States are affected by diabetes or prediabetes (Cowie et al., 2009), and the health consequences of poor glycemic control are severe. Blood glucose tracking applications for mobile devices have the potential to help improve glycemic control but design issues may limit their use by older adults. We examined the usability of three existing blood glucose tracking applications via hierarchical task analysis and heuristic evaluation of their graph displays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…[10] In another recent study, Whitlock and McLaughlin studied three apps for tracking blood glucose and found that each product may present a number of usability issues, including small text, poor color contrast and scrolling wheels, especially for older adults. [11] As a result, further research needs to be done to ensure that mobile health technologies are appropriately designed and targeted to the end-users’ needs before they are used as health interventions. [12] Prior to the trial of mHealth technologies for improving clinical outcomes, it is imperative that IT designers pay close attention to the usability of these technologies.…”
mentioning
confidence: 99%
“…[10] In another recent study, Whitlock and McLaughlin studied three apps for tracking blood glucose and found that each product may present a number of usability issues, including small text, poor color contrast and scrolling wheels, especially for older adults. [11] As a result, further research needs to be done to ensure that mobile health technologies are appropriately designed and targeted to the end-users’ needs before they are used as health interventions. [12] Prior to the trial of mHealth technologies for improving clinical outcomes, it is imperative that IT designers pay close attention to the usability of these technologies.…”
mentioning
confidence: 99%
“…Similarly, the legibility of axis labels, annotations, and other text is an important consideration when designing visualizations for older adults. Reading smaller fonts grows progressively difficult with Age [JF17b] and several studies point to older adults' challenges using visualizations due to this issue [FWX*23,MSC*19,WM12]. Enlarging font size is an immediate solution for legibility issues, but may not always be feasible due to constraints such as limited screen real state (e.g., smartwatch).…”
Section: State Of the Practice In Gerontovismentioning
confidence: 99%
“…Morey et al [MSC*19] evaluated the accessibility of two popular mobile health apps, learning that both apps had low color contrast that hindered their usability for older adults. Whitlock and McLaughlin [WM12] discovered similar contrast and color choice issues during a hierarchical task analysis on three mobile health (mHealth) apps, recommending a change of dark‐grey‐on‐light‐grey text and lines to black‐on‐white based on existing accessibility guidelines for older adults [FCC*04, PM10]. Fan et al [FWX*23] also identified low contrast as a design issue that hindered older adults' ability to gain insights from online COVID‐19 visualizations.…”
Section: State Of the Practice In Gerontovismentioning
confidence: 99%
“…To empower older adults with self-care capabilities, mHealth apps generally have several features, including health information delivery, appointment and medication reminders, and monitoring of vital signs. 1 , 2 , 3 , 4 There is evidence that more older adults nowadays are willing to use their smartphones to better manage their own health. 5 , 6 A recent report indicated that introducing mHealth may improve the efficiency of health care for older adults by 20%, suggesting that using a smartphone is a viable way to move the health promotion process forward.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of mobile health (mHealth) smartphone apps has ushered in an innovative way for older adults to improve their health and prevent deterioration from chronic diseases. To empower older adults with self-care capabilities, mHealth apps generally have several features, including health information delivery, appointment and medication reminders, and monitoring of vital signs . There is evidence that more older adults nowadays are willing to use their smartphones to better manage their own health .…”
Section: Introductionmentioning
confidence: 99%